Contribution of cats and dogs to SARS-CoV-2 transmission in households - Egil A. J. Fischer; Els M. Broens; Hans S. Kooistra; Myrna M. T. De Rooij; Jan Arend Stegeman; Mart C. M. De Jong (Frontiers in Veterinary Science, 2023)
IntroductionSARS-CoV-2 is known to jump across species. The occurrence of transmission in households between humans and companion animals has been shown, but the contribution of companion animals to the overall transmission within a household is unknown. The basic reproduction number (R0) is an important indicator to quantify transmission. For a pathogen with multiple host species, such as SARS-CoV-2, the basic reproduction number needs to be calculated from the partial reproduction numbers for each combination of host species.MethodIn this study, the basic and partial reproduction numbers for SARS-CoV-2 were estimated by reanalyzing a survey of Dutch households with dogs and cats and minimally one SARS-CoV-2-infected human.ResultsFor households with cats, a clear correlation between the number of cats and the basic reproduction number (Spearman's correlation: p 0.40, p-value: 1.4 × 10−5) was identified, while for dogs, the correlation was smaller and not significant (Spearman's correlation: p 0.12, p-value: 0.21). Partial reproduction numbers from cats or dogs to humans were 0.3 (0.0–2.0) and 0.3 (0.0–3.5) and from humans to cats or dogs were 0.6 (0.4–0.8) and 0.6 (0.4–0.9).DiscussionThus, the estimations of within-household transmission indicated the likelihood of transmission from these companion animals to humans and vice versa, but the observational nature of this study limited the ability to establish conclusive evidence. This study's findings support the advice provided during the pandemic to COVID-19 patients to maintain distance from companion animals as a precautionary measure and given the possibility of transmission, although there is an overall relatively limited impact on the pandemic when compared to human-to-human transmission.